In defense of globalization - Bhagwati, Jagdish N., 1934- (New York : Oxford University Press, 2004)
Publisher's description: The riot-torn meeting of the World Trade Organization in Seattle in 1999 was only the most dramatic sign of the intensely passionate debate now raging over globalization, which critics blame for everything from child labour to environmental degradation, cultural homogenization, and a host of other ills afflicting poorer nations. Now Jagdish Bhagwati, the internationally renowned economist known equally for the clarity of his arguments and the sharpness of his pen, takes on the critics, revealing that globalization, when properly governed, is in fact the most powerful force for social good in the world today. Drawing on his unparalleled knowledge of international economics, Bhagwati explains why the'gotcha' examples of the critics are often not as they seem, and that in fact globalization often alleviates many of the problems for which it has been blamed. For instance, when globalization leads to greater general prosperity in an underdeveloped nation, it quickly reduces child labour and increases literacy (when parents have sufficient income, they send their children to school, not work). The author describes how globalization helps the cause of women around the world and he shows how economic growth, when coupled with the appropriate environmental safeguards, does not necessarily increase pollution. And to counter the charge that globalization leads to cultural hegemony, to a bland'McWorld,' Bhagwati points to the example of Salman Rushdie, a writer who blends Bombay slang and impeccable English in novels touched by magic realism borrowed from South American writers. Globalization leads not to cultural white bread but to a spicy hybrid of cultures. With the wit and wisdom for which he is renowned, Bhagwati convincingly shows that globalization is part of the solution, not part of the problem. Anyone who wants to understand what's at stake in the globalization wars must read In Defense of Globalization.
'A Council on Foreign Relations Book.'
Includes bibliographical references and index.
Keywords: Globalization -- Economic aspects; Globalization -- Social aspects; Anti-globalization movement